A review of the Bank of Canada's support of key financial markets during the COVID-19 crisis - Joshua Fernandes; Michael Mueller (Bank of Canada, 2023)
The COVID-19 pandemic placed unprecedented strain on the global financial system. We describe how the Bank of Canada responded to the rapidly deteriorating liquidity in core Canadian fixed-income markets. We also describe how market functioning improved after the Bank intervened. The Bank implemented several emergency facilities to ease market-wide liquidity strains, restore market functioning and support the stabilization and recovery of the Canadian economy. Over time, market functioning improved, and liquidity returned to prepandemic levels. The Bank's facilities helped resolve market dysfunction and ensured that credit continued to be extended to households and businesses.
Keywords: E44; E58; G01; 330; Coronavirus disease (COVID-19); Financial markets; Market structure and pricing; Monetary policy and uncertainty